Saturn's quasiperiodic magnetohydrodynamic waves. Issue 21 (3rd November 2016) - Yates, J. N.; Southwood, D. J.; Dougherty, M. K.; Sulaiman, A. H.; Masters, A.; Cowley, S. W. H.; Kivelson, M. G.; Chen, C. H. K.; Provan, G.; Mitchell, D. G.; Hospodarsky, G. B.; Achilleos, N.; et al.
Abstract: Quasiperiodic ∼1 h fluctuations have been recently reported by numerous instruments on board the Cassini spacecraft. The interpretation of the sources of these fluctuations has remained elusive to date. Here we provide an explanation for the origin of these fluctuations using magnetometer observations. We find that magnetic field fluctuations at high northern latitudes are Alfvénic, with small amplitudes (∼0.4nT), and are concentrated in wave packets similar to those observed in Kleindienst et al. (2009). The wave packets recur periodically at the northern magnetic oscillation period. We use a magnetospheric box model to provide an interpretation of the wave periods. Our model results suggest that the observed magnetic fluctuations are second harmonic Alfvén waves standing between the northern and southern ionospheres in Saturn's outer magnetosphere. Key Points: Cassini observed quasiperiodic ∼60 min (QP60) fluctuations of Saturn's magnetic field These fluctuations are consistent with similar QP60 pulsations reported at Saturn We propose that these fluctuations are standing second harmonic Alfvén waves